Antiplasmodial activity of flavan derivatives from rootbark of Cassia abbreviata Oliv. - David M. Kiplagat; Hoseah M. Akala; Pamela O. Liyala; Julia M. Wangui; Rose A.O. Odhiambo; Josiah O. Omolo (Journal of Saudi Chemical Society)
The root bark of Cassia abbreviata has been traditionally used by the native population of the coastal region of Kenya to treat malaria. As part of our ongoing investigations into compounds with activity against malaria parasites, we tested the in vitro antiplasmodial activity against Plasmodium falciparum strain namely; chloroquine-resistant W2 and chloroquine-sensitive D6. The methanolic root extract of the plant was active against the chloroquine-sensitive (IC50 = 20.56 μg/ml) and the chloroquine-resistant (IC50 = 13.31 μg/ml) strains of P. falciparum. Two flavans 1 and 2 were purified, identified and further shown to be antiplasmodial. Compound 2 was more active than compound 1 against both strains of P. falciparum with IC50 values of 8.12 μg/ml (D6); 8.89 μg/ml (W2) and 26.02 μg/ml (D6); 25.97 μg/ml (W2), respectively. This study partly provides evidence to support the use of C. abbreviata as a malaria remedy, as used by the native populations.